حرية الإعلام والمعالجة الإعلامية للحراك الشّعبي في الجزائر - عباسي . ., أحمد المبارك; مصطفاوي, بوبكر (University of Eloued جامعة الوادي, 2022)
تعالج هذه الورقة البحثيّة الموسومة بـ “حريّة الإعلام والحراك الشّعبي في الجزائر" حريّة الإعلام والتّغيرات التي مسّته في الجزائر منذ الحراك الشّعبي، والإطار المفاهيمي لوسائل الإعلام وأهم وظائفها، والحراك الشّعبي ومشروعيّته في الفقه الإسلامي والمواثيق والمعاهدات الدّولية والقانون الجزائري، وتأثيره في وسائل الإعلام بتناول قضايا الشَّأن العام. وتطرّق البحث إلى مناقشة الإشكاليّة التي ترمي إلى معرفة مدى التّأثير الذي أحدثه الحراك الشّعبي في الجزائر على وسائل الإعلام وكيفيّة معالجتها لأحداثه، وهل تحرّرت وسائل الإعلام من توجيهات ورقابة السّلطة وانتظمت بالقوانين؟ وهل توجّهت نحو التزام المصداقيّة والموضوعيّة؟ وخلصت الدّراسة إلى عدّة نتائج أهمّها: أنّ الحراك الشّعبي السّلمي صورة من صور التّظاهر المشروعة فقهاً وقانوناً، كذلك حريّة الإعلام في الجزائر يقرّها الدّستور غير أنّها مازالت بعيدة عن المصداقيّة والموضوعيّة. Abstract: This research paper entitled “Media freedom and popular movement in Algeria,” discusses the freedom of the media and the changes that have affected it in Algeria since the popular movement, the conceptual framework of the media and its most important functions, also the popular movement and its legitimacy in Islamic jurisprudence, international treaties, and Algerian law, moreover its impact on the media by addressing issues Public affairs. The research paper dealt with the discussion of the problem that aimed to know the extent of the influence that the popular movement in Algeria had on the media and how they dealt with its events, and have the media freed from the authority's directives and control and were organized with laws. Was it directed towards a commitment to credibility and objectivity? The study concluded with several conclusions, which are summarized: that the peaceful popular movement is a form of legitimate protest, both in jurisprudence and law, as well as the freedom of the media in Algeria is recognized by the constitution, but it is still far from credibility and objectivity.
Media Freedom and Media treatment of the popular movement in Algeria
مقال
Keywords: وسائل الإعلام؛ الحراك الشّعبي؛ المعالجة الإعلامية؛ دور الإعلام.; media freedom; popular movement; Informational processing; Islamic jurisprudence, law